Shenling Baizhu San ameliorates non-alcoholic fatty liver disease in mice by modulating gut microbiota and metabolites - Chen, Dongliang; Wang, Yuanfei; Yang, Jianmei; Ou, Wanyi; Lin, Guiru; Zeng, Ze; Lu, Xiaomin; Chen, Zumin; Zou, Lili; Tian, Yaling; Wu, Aiping; Keating, Shelley E.; et al. (Frontiers in Pharmacology, 2024)
Purpose: The prevalence of non-alcoholic fatty liver disease (NAFLD) and its related mortality is increasing at an unprecedented rate. Traditional Chinese medicine (TCM) has been shown to offer potential for early prevention and treatment of NAFLD. The new mechanism of “Shenling Baizhu San” (SLBZS) is examined in this study for the prevention and treatment of NAFLD at the preclinical level. Methods: Male C57BL/6J mice were randomly divided into three groups: normal diet (ND), western diet + CCl4 injection (WDC), and SLBZS intervention (WDC + SLBZS). Body weights, energy intake, liver enzymes, pro-inflammatory factors, and steatosis were recorded in detail. Meanwhile, TPH1, 5-HT, HTR2A, and HTR2B were tested using qRT-PCR or ELISA. Dynamic changes in the gut microbiota and metabolites were further detected through the 16S rRNA gene and untargeted metabolomics. Results: SLBZS intervention for 6 weeks could reduce the serum and liver lipid profiles, glucose, and pro-inflammatory factors while improving insulin resistance and liver function indexes in the mice, thus alleviating NAFLD in mice. More importantly, significant changes were found in the intestinal TPH-1, 5-HT, liver 5-HT, and related receptors HTR2A and HTR2B. The 16S rRNA gene analysis suggested that SLBZS was able to modulate the disturbance of gut microbiota, remarkably increasing the relative abundance of probiotics (Bifidobacterium and Parvibacter) and inhibiting the growth of pro-inflammatory bacteria (Erysipelatoclostridium and Lachnoclostridium) in mice with NAFLD. Combined with metabolomics in positive- and negative-ion-mode analyses, approximately 50 common differential metabolites were selected via non-targeted metabolomics detection, which indicated that the targeting effect of SLBZS included lipid metabolites, bile acids (BAs), amino acids (AAs), and tryptophan metabolites. In particular, the lipid metabolites 15-OxEDE, vitamin D3, desoxycortone, and oleoyl ethanol amide were restored by SLBZS. Conclusion: Integrating the above results of multiple omics suggests that SLBZS ameliorates NAFLD via specific gut microbiota, gut-derived 5-HT, and related metabolites to decrease fat accumulation in the liver and inflammatory responses.